2021
DOI: 10.1007/s00240-021-01271-5
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopic surgery for treatment of urinary tract stones in children: report of a multicenter international experience

Abstract: This study aimed to report a multi-institutional experience with robot-assisted laparoscopic surgery (RALS) for treatment of urinary tract stones in children. The medical records of 15 patients (12 boys), who underwent RALS for urolithiasis in 4 international centers of pediatric urology over a 5-year period, were retrospectively collected. The median patient age was 8.5 years (range 4–15). Eleven/fifteen patients (73.3%) had concurrent uretero–pelvic junction obstruction (UPJO) and 2/15 patients (13.3%) had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
(58 reference statements)
0
21
0
3
Order By: Relevance
“…Although the majority of children with urinary stones are managed via ESWL, URS, RIRS, or PCNL, the use of MIS has significantly increased over the last two decades ( 27 , 28 ).…”
Section: Robotic-assisted Laparoscopic Proceduresmentioning
confidence: 99%
“…Although the majority of children with urinary stones are managed via ESWL, URS, RIRS, or PCNL, the use of MIS has significantly increased over the last two decades ( 27 , 28 ).…”
Section: Robotic-assisted Laparoscopic Proceduresmentioning
confidence: 99%
“…Since then, many studies have confirmed the safe and efficient use of both modalities in the treatment of pediatric bladder stones. Recently, minimally invasive surgery (MIS) has shown to be safe and effective in removing big bladder stones [11]. The superior advantage of MIS is the possibility of removing bladder stones through the navel, utilizing an endobag, without crushing them [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, minimally invasive surgery (MIS) has shown to be safe and effective in removing big bladder stones [11]. The superior advantage of MIS is the possibility of removing bladder stones through the navel, utilizing an endobag, without crushing them [11]. Moreover, robot-assisted laparoscopic surgery has demonstrated efficacy in the treatment of large-volume stones, especially in conditions requiring simultaneous reconstruction [12].…”
Section: Introductionmentioning
confidence: 99%
“…Open or laparoscopic approaches are seldom used, especially trans parenchymal approaches, due to their greater invasiveness. Several series exist for robot-assisted laparoscopic approaches to stones in children in the non-PH population [ 1 , 2 ]. This may work well for selected patients as a one-time treatment.…”
mentioning
confidence: 99%
“…Reoperative robotic pyeloplasty in children takes longer and has a longer associated length-of-stay [ 3 , 4 ], as well as a higher rate of complications than comparable series of primary cases [ 4 , 5 ]. Similarly, the stone procedures reported are largely in older children and teens [ 1 , 2 ]; patients with PH often present as infants and toddlers, creating additional surgical challenge and risk.…”
mentioning
confidence: 99%